Propuesta para la reutilización de aguas de rechazo del sistema de purificación empleado en la empresa casa del agua en Santa Marta (2021)
The company CASA DEL AGUA for water purification uses the reverse osmosis system, which is designed to eliminate salts, particles, viruses and others, which are present in the water. It is based on a membrane that divides two media through which the water passes, leaving a concentrated medium (rejection) and a concentration-free medium (product). For this reason, a high percentage of water rejection is obtained, sent to the sanitary drainage, impacting the environment in a negative way. On the other hand, after the water purification process is finished, the company has programmed a backwash with purified water in order to clean the filters three times a week with a period of thirty minutes each backwash in such a way sending the water to the sanitary sewer regardless of the water conditions. The purpose of this research work is to propose alternatives for the reuse of water rejected by the purification system implemented by the Casa Del Agua Company in the city of Santa Marta, obtaining an ecological benefit, providing methods and strategies that allow it to be put to a new use. Scarce resource. To solve the proposed objective, three phases were carried out, which were developed in order to choose the best alternative for the viability of the project proposed to the company.